Cervical Pap screening among women living with HIV in Puerto Rico and the United States - Medical Monitoring Project, 2018-2021 - Marievelisse Soto-Salgado; Lorena González-Sepúlveda; Maritza Cruz-Cortés; Michael I. Rivera-Morales; Sharee Umpierre; Jane R. Montealegre; Ana P. Ortiz (Elsevier, 2024)
Our objective was to determine the prevalence of cervical Pap screening among women living with HIV (WLWH) in Puerto Rico (P.R.) and other selected United States (U.S.) jurisdictions. Additionally, we sought to compare selected characteristics of WLWH who underwent cervical Pap screening between P.R. and the other U.S. jurisdictions. We analyzed data from the 2018-2021 cycles of CDC's Medical Monitoring Project (MMP), a national surveillance system among adults with HIV residing in P.R. (n = 218) and 22 other MMP jurisdictions (n = 3,653). Weighted percentages and 95 % confidence intervals (CIs) for selected characteristics were estimated. Prevalence ratios with predicted marginal means were calculated. An estimated 91.6 % and 84.6 % of WLWH underwent cervical Pap screening in P.R. and the other 22 MMP jurisdictions, respectively (Prevalence Ratio = 1.08, 95% CI = 1.03-1.13). Among WLWH who underwent cervical Pap screening, those in P.R. were more likely to be 50+ years of age, have a household annual income below $20,000, engage in binge drinking, never smoke, and have Medicaid/other public insurance than those in the other 22 MMP jurisdictions (p < 0.05). No differences were found between P.R. and the other 22 MMP jurisdictions in the percentage reporting higher than the median HIV-stigma score, experiencing HIV health care discrimination, and having ≥ 1 sexual partner in the past 12 months. Although cervical Pap screening rates among WLWH were higher in P.R. than in the other 22 MMP jurisdictions, both surpass the Healthy People 2030 target. Future research should assess adherence and compliance with updated cervical cancer screening guidelines.